Synchrotron X-ray fluorescence imaging study on chloride-induced stress corrosion cracking behavior of austenitic stainless steel welds via selective corrosion of δ-ferrite. (1st July 2023) - Kim, Seunghyun; Ahn, Kangwoo; Kim, Gidong; Song, Sang-Woo
Abstract: Chloride-induced stress corrosion cracking (CISCC) is a degradation of austenitic stainless steels by Cl-containing media, residual stress, and materials susceptibility. In this study, synchrotron X-ray fluorescence imaging and electron microscopy were utilized to investigate the CISCC mechanism in austenitic stainless steel welds 304 L -ER308L and 316 L -ER316L. Specimens were exposed to 60 °C and 30% relative humidity conditions for 3 months and their microstructure and chemistry were analyzed. Since δ-ferrite is composed of ferrite formers especially Cr and acts as a sink for impurities, selective corrosion of δ-ferrite results in pitting corrosion and CISCC propagation. Graphical Abstract: ga1 Highlights: Chloride-induced stress corrosion cracking behavior of ER308L and ER316L is studied. In cyclic corrosion chamber, the alloys are exposed for 12 weeks in 60 °C, 30 RH%. SEM, TEM, EPMA and synchrotron XRF imaging are exploited for the analysis. Cracking is only observable for ER308L while only corrosion occurs in ER316L. Selective corrosion δ-ferrite in ER308L induces the propagation of the cracks.